Does Bicanalicular Intubation Improve the Outcome of Endoscopic Dacryocystorhinostomy? - Matoušek, Petr; Lubojacký, Jakub; Masárová, Michaela; Čábalová, Lenka; Červenka, Stanislav; Komínek, Pavel (Journal of clinical medicine, 2022)
UNLABELLED: The aim of this study was to compare the success of endoscopic dacryocystorinostomy with and without bicanalicular intubation in the treatment of distal nasolacrimal duct obstruction. METHODS: In a prospective, randomized, comparative study, endoscopic dacryocystorinostomy without bicanalicular silicone intubation (Group I) and endoscopic dacryocystorinostomy with intubation (Group II) were performed in patients with distal nasolacrimal duct obstructions. The tubes were removed 3 months after surgery in Group II, and the patients were followed up for 6 months after surgery. Therapeutic success was defined as the fluorescein dye disappearance test grade 0-1 corresponding with a complete resolution of symptoms. RESULTS: Thirty patients, aged 23-86 years, were included in the study. The success rate was 13/15 (86.67%) in Group I and in 14/15 (93.33%) in Group II. The difference between the two groups was not statistically significant (p = 0.483). Most common complications were granulations that occurred in 1/15 (6.67%) patient in Group I and in 2/15 (13.33%) patients in Group II. Adhesions in rhinostomy with epiphora and persistent secretion were observed in 1/15 (6.67%) patient in Group II. CONCLUSIONS: Bicanalicular intubation does not significantly increase the success rate of EDCR in distal nasolacrimal obstruction in adults.
Keywords: distal nasolacrimal duct obstruction; endoscopic dacryocystorhinostomy; bicanalicular intubation